Mitigation of salt stress on low temperature in bermudagrass: resistance and forage quality - Zhou, Xiuwen; Yin, Yanling; Wang, Guangyang; Amombo, Erick; Li, Xiaoning; Xue, Ying; Fu, Jinmin (Frontiers in Plant Science, 2022)
Climate change causes plants encountering several abiotic stresses simultaneously. Responses of plants to a single stress has been comprehensively studied, but it is hard to speculated infer the effects of stress combination based on these researches. Here, the response mechanism of bermudagrass to low temperature and salt treatment was investigated in this study. The results showed that low temperature (LT) treatment decreased the relative growth rate, chlorophyll fluorescence transient curve, biomass, and crude fat content of bermudagrass, whereas low temperature + salt (LT+S) treatment greatly undermined these declines. Furthermore, at 6 h and 17 d, the expression levels of glyoxalase I (GLYI), Cu-Zn/superoxide dismutase (Cu-Zn/SOD), peroxidase 2 (POD2), and oxidative enzyme 1(CAT1) in roots were considerably higher in the low temperature + salt treatment than in the low temperature treatment. Low temperature stress is more detrimental to bermudagrass, but mild salt addition can mitigate the damage by enhancing photosynthesis and improving the expression of antioxidant system genes (Cu-Zn/SOD, POD2 and CAT1) and glyoxalase system GLYI gene in roots. This study summarized the probable interaction mechanism of low temperature and salt stress on bermudagrass, which can provide beneficial reference for the growth of fodder in cold regions.